(untitled) (Research, Society and Development, 2020)
Hydrologic simulation is an important tool for the planning and management of water resources. However, the lack of input data, particularly soil and climate data, frequently complicates the application of hydrological models in Brazilian Atlantic Rainforest basins. The purpose of this study was to analyse the application of the VIC model, under the condition of low data availability, to predict the daily streamflow of two basins (Jucu and Santa Maria da Vitória). The results showed satisfactory statistical indexes only for the Santa Maria da Vitória basin. Due to data limitations and the simplified forms used to estimate these missing data, the model proved promising for understanding the hydrologic regime of these basins.